Critical Raw Materials and Economic Complexity in Latin America - Lara Rodríguez, Juan Sebastián; Tosi Furtado, André; Altimiras-Martin, Aleix (Universidad Pedagógica y Tecnológica de Colombia, 2018)
There are minerals that boost economic growth and which are essential for the development of sustainable technologies. These critical raw materials (CRMs) were determined by models created for complex economies. This paper aims to examine the mineral policies regarding CRMs of the main Latin-American economies, and the role of their respective National Innovation Systems (NIS) in the pursuit of greater economic complexity. This is achieved through a comparative assessment method applied to the mineral policies of the principal nations of the region —Brazil, Mexico, Argentina, Colombia and Chile. In this way, we found that due to the simplicityof these economies, as well as mineral policies that disregard their respective NIS, the increase of the economic complexity of the states in question is compromised. This is characterized by the exiguous value added through the interaction of knowledge and capabilities regarding their mineral resources and industry.